English Capital Letters Recognition Depends On Computing The Seven Moments (Al-Mansour Journal, 2022)
There are many digital images for printed documents and the research will continue to arrive to the bestalgorithm for identifying the English characters symbols and those letters more frequently. There has been a greatarea for these researches. This research uses an image that contains single character each. The proposedrecognition process begins by converting that image into frequency domain by applying discrete cosinetransform(DCT) , computing the seven moments for this image as a features for that character and then building adatabase which depends on these features for recognition task. The aim of this research is to prove that each capitalletter has been written with the same font and size but in different directions is also one of the English capital letterbecause it has the same seven moment’s values.
Keywords: Discrete Cosine Transform; Rules of moments; Digital image contains single English letter